2021
DOI: 10.1128/mra.00521-21
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Alcaligenes faecalis HZ01, with Potential to Inhibit Nontuberculous Mycobacterial Growth

Abstract: Alcaligenes faecalis is a Gram-negative rod that is ubiquitous in the environment and is an opportunistic human pathogen. Here, we report the whole-genome sequencing analysis of A. faecalis HZ01, which presents mycobacterial growth inhibitory activity and was isolated from a contaminated culture of Mycobacterium chubuense ATCC 27278.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The HA-negative mutant strain, A. ammonioxydans 2-29, showed no antagonism and reconstituting this mutant with the intact dnfR gene restored the ability to inhibit the growth of V4 cells, indicating that HA was the key molecule in this process. Since other Alcaligenes species are potential candidates in the production of antibacterial substances (Felestrino et al, 2020;Fernandes et al, 2021), it is tempting to speculate that other antagonistic secondary metabolites existed. The degradation of HA beyond ∼24 h of culture, while some antagonism could still be observed beyond this time point suggested that this may be the case especially during the late growth stage of HO-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HA-negative mutant strain, A. ammonioxydans 2-29, showed no antagonism and reconstituting this mutant with the intact dnfR gene restored the ability to inhibit the growth of V4 cells, indicating that HA was the key molecule in this process. Since other Alcaligenes species are potential candidates in the production of antibacterial substances (Felestrino et al, 2020;Fernandes et al, 2021), it is tempting to speculate that other antagonistic secondary metabolites existed. The degradation of HA beyond ∼24 h of culture, while some antagonism could still be observed beyond this time point suggested that this may be the case especially during the late growth stage of HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Many B. velezensis strains gained practical application in promoting plant growth and antagonizing pathogens (Fan et al, 2018). Alcaligenes species are another group of potential PGPR (Yokoyama et al, 2013;Ray et al, 2016;Gong et al, 2019;Lahlali et al, 2020), with distinct biotechnological potential in the pharmaceutical industry and bioremediation of contaminated environments (Ray et al, 2015;Dixit et al, 2020;Felestrino et al, 2020;Onajobi et al, 2020;Zouari et al, 2020;Fernandes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%